Antimicrobial Activity Profiles and Potential Antimicrobial Regimens against Carbapenem-Resistant Enterobacterales Isolated from Multi-Centers in Western Thailand - Parnrada Nulsopapon; Manat Pongchaidecha; Worapong Nasomsong; Pitimon Polwichai; Sirilada Suphankong; Pantip Sirichote; Siriwan Chaisomboonpan; Wichai Santimaleeworagun (MDPI AG, 2022)
The spread of carbapenem-resistant Enterobacterales (CRE) constitutes a global health burden. Antimicrobial susceptibility and types of carbapenemase differ by geographic region. This study aimed to (1) examine the minimum inhibitory concentrations (MICs) and antibiotic resistance genes and (2) investigate antibiotic dosing regimens against CRE using Monte Carlo simulation. Clinical carbapenem-resistant Klebsiella pneumoniae (CRKP), Escherichia coli (CREC), and Enterobacter cloacae (CREclo) isolates were collected from various hospitals in western Thailand. Broth microdilution was performed, and the types of carbapenemase and mcr-1 genes were detected using polymerase chain reaction (PCR). Monte Carlo simulation was used to establish optimal antimicrobial dosing regimens meeting the criterion of a cumulative fraction of response (CFR) >90%. A total of 150 CRE isolates from 12 hospitals were included. The proportion of CRKP (76%) was greater than that of CREC (22%) and CREclo (2%). Regional hospitals reported higher rates of resistance than general hospitals. Most isolates were resistant to aztreonam and ceftazidime/avibactam, whereas they were highly susceptible to aminoglycosides. Most carbapenemases were NDM (47.33%), OXA-48 (43.33%) and NDM plus OXA-48 (6.67%); five OXA-48 positive isolates carried mcr-1 genes. Currently, high-dose tigecycline is the only optimal regimen against CRE isolates. Further extensive research on antibiotic synergism or new antibiotics should be conducted.